Prenatal prediction of spinal muscular atrophy. Issue 3 (March 1992) - Daniels, R J; Suthers, G K; Morrison, K E; Thomas, N H; Francis, M J; Mathew, C G; Loughlin, S; Heiberg, A; Wood, D; Dubowitz, V
Abstract : Spinal muscular atrophy (SMA) is a common cause of inherited morbidity and mortality in childhood. The wide range of phenotypes in SMA, uncertainty regarding its mode of inheritance, and the suggestion of linkage heterogeneity have complicated the genetic counselling of parents of affected children. The locus responsible for autosomal recessive SMA has been mapped to 5q11.2-q13.3. The most likely order of loci is cen-D5S6-(SMA, D5S125)-(JK53CA1/2, D5S112)-D5S3 9-qter, with highly polymorphic loci being identified at JK53CA1/2 and D5S39. We describe linkage studies with another highly polymorphic locus, D5S127, that is closely linked to D5S39. This genetic map can be used as the basis for genetic counselling in families with autosomal recessive SMA. Appropriate allowance can be made for sporadic cases owing to non-inherited causes and for linkage heterogeneity or misdiagnoses.